The Role of Small-Scale Industries in Achieving the Sustainable Development: the Experience of India - N. V. Galistcheva (Vestnik MGIMO-Universiteta)
The article deals with the role of small scale industry in India in achieving the sustainable development. The author draws attention to the fact that the small scale industry promotion policy impacts significantly not only on decreasing the unemployment rate as well as long-term and youth unemployment but also on solving such acute social problems as poverty, famine, undernourishment and food insecurity, lack of quality education, gender inequality and the empowerment of women. The author pays attention to the evolution of small business in India in 1950-2010s. It argues convincingly that due to significant number of population as well as low-skilled labor on the one hand and limited financial resources on the other one small business has been considered to be a buffer between modern big business and the bulk of the population remaining outside it. The author considers the effectiveness of the industrial policy through the prism of stimulating small-scale industry and changing its place in the Indian economy. The author examines the activity of the The National Bank for Agricultural and Rural Development (NABARD) which is considered to be the most important institution which looks after the development of the small scale industries. The aim of NABARD was poverty reduction and development assistance (it’s one of the premier agencies providing developmental credit in rural areas). The article presents the definition of small scale industry in India both in terms of employment level and the investment limits as well as statistical data on number of units, its share in industrial production and exports and expansion of small scale sector in 2000-2010s. The author identified main problems facing cottage and small scale industries in India at the present time. The research is based on the systematic approach to the study of national economy using basic methods of scientific knowledge such as induction and deduction, analysis and synthesis.